2017
DOI: 10.1063/1.4973651
|View full text |Cite
|
Sign up to set email alerts
|

Cooling of isolated anthracene cations probed with photons of different wavelengths in the Mini-Ring

Abstract: We report on a direct measurement of the Internal Energy Distribution (IED) shift rate of an initially hot polycyclic aromatic hydrocarbon (PAH) molecular ensemble, anthracene cations (CH). The ions were produced in an electron cyclotron resonance (ECR) ion source and stored in an electrostatic ion storage ring, the Mini-Ring. Laser pulses of two wavelengths were sent successively to merge the stored ion bunch at different storage times to enhance the neutral fragment yield due to fast laser induced dissociati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Gas phase experiments performed in a storage ring device, mimicking the conditions encountered by this molecule in the outer space, have shown that a beam of (C 14 H 10 ) + cools down radiatively at rates of around 200 s −1 upon laser excitation. These rates are two orders of magnitude higher than those expected from vibrational transitions, thus suggesting transitions of electronic nature via the RF mechanism [102][103][104][105].…”
Section: Decays Of Carbon-based Clustersmentioning
confidence: 74%
“…Gas phase experiments performed in a storage ring device, mimicking the conditions encountered by this molecule in the outer space, have shown that a beam of (C 14 H 10 ) + cools down radiatively at rates of around 200 s −1 upon laser excitation. These rates are two orders of magnitude higher than those expected from vibrational transitions, thus suggesting transitions of electronic nature via the RF mechanism [102][103][104][105].…”
Section: Decays Of Carbon-based Clustersmentioning
confidence: 74%
“…Since the turn of the century, radiative cooling rates of clusters have been inferred from experiments probing time-dependent spontaneous neutralization rates of ensembles of hot ions stored in electrostatic ion-beam storage devices (see e.g. [12][13][14][15][16][17][18][19][20][21]). Such devices have been used to isolate and probe the cooling of cluster ions for durations of up to tens of milliseconds.…”
Section: Introductionmentioning
confidence: 99%
“…The derivation of the power law decay is fairly general, and it has been observed in a number of experimental studies, most often at relatively short times (Hansen & Echt, 1997;Andersen et al, 2001;Hansen et al, 2001;Andersen et al, 2003a, b;Tomita et al, 2003;Andersen, Heber, & Zajfman, 2004;Fedor et al, 2005;Toker et al, 2007;Sundén et al, 2009;Froese et al, 2011;Lange et al, 2012;Goto et al, 2013;Martin et al, 2013;Najafian et al, 2014;Martin et al, 2015;Breitenfeldt et al, 2016;Hansen et al, 2017b;Ji et al, 2017;Martin et al, 2017;Anderson et al, 2018;Bernard et al, 2019). However, corrections may arise to these results, both in the power of −1 and in the long term behavior, caused by factors both intrinsic and external to the decaying system.…”
Section: Modification Of 1/t Rates: Intrinsic Source Propertiesmentioning
confidence: 94%
“…These aspects are by now well established experimentally, primarily by work at ion storage rings (Andersen et al, 1996(Andersen et al, , 2001Hansen et al, 2001;Tomita et al, 2001;Andersen et al, 2003a;Andersen, Heber, & Zajfman, 2004;Fedor et al, 2005;Toker et al, 2007;Froese et al, 2011;Lange et al, 2012;Toker et al, 2012;Martin et al, 2013;Menk et al, 2014;Martin et al, 2015;Breitenfeldt et al, 2016;Hansen et al, 2017b;Ji et al, 2017;Martin et al, 2017;Anderson et al, 2018;Bernard et al, 2019;Martin et al, 2019), occasionally in a form where other channels are present, but also at single pass devices such as time-offlight mass spectrometers (Hansen & Campbell, 1996;Hansen & Echt, 1997;Ferrari et al, 2015;Hansen et al, 2017a;Ferrari et al, 2018a, b), and here the focus will be on the theoretical aspects.…”
Section: Introductionmentioning
confidence: 98%